Equilibrium and Stability of Nonlinearly Elastic Cylinder Made of Blatz-Ko Material - Leonid Pavlovich OBREZKOV (Engineering Transactions)
The Blatz-Ko model describing the behavior of nonlinearly elastic compressible material was used to model the process of stretching and inflation of hollow cylinder, both thick- and thin-walled. By means of semi-inverse method, the three-dimensional problem was reduced to the analysis of boundary-value problem for ordinary differential equation of second order. The presented numerically constructed loading diagrams show in this the model that even the regions of positive stresses can contain zones of instability. Within the framework of bifurcation analysis, size of these zones and their dependence on material parameters were determined.